Pemahaman Siswa Tentang Informasi Karir Jurusan Pariwisata dan Upaya Guru BK di SMK Nusatama Padang - Susanti, Eni; S, Neviyarni; Marjohan, Marjohan (Konselor, 2015)
Counselor is one of the educators who assist students in understanding their career will live in the future. Specifically for vocational students, information about the types of careers that have been linked to employment, position or career aspired after completing studies in education are taken. The purpose of this study to describe: 1) understanding students majoring in Tourism Vocational Nusatama Padang on the type of career information and a description of the types of careers, 2) attempts to provide insight counselor to students about careers Nusatama SMK Padang Tourism department. The population was 156 students. The number of sample was 111 students and have been using cluster random sampling technique. The findings of the study are: 1) students understand the types of careers and career descriptions are in the middle category, 2) counselor need to further improve the students in understanding the type and career description. Therefore counselors need to improve guidance and counseling services related to an increase students' understanding of career information and descriptions of tourism department, so students are prepared to enter the workforce. Â